PRANATA SOSIAL DAN PEMBENTUKAN DIRI HOMOSEKSUAL TOKOH KUSAKABE HIKARU DALAM MANGA DOUKYUUSEI KARYA NAKAMURA ASUMIKO - widya fahrani; Tienn Immery; Irma (Hikari: Jurnal Bahasa dan Kebudayaan, 2021)
This research chose Doukyuusei vol 1-3 manga by Nakamura Asumiko because it depicts the stage of homosexual self formation of Kusakabe Hikaru. The stage of homosexual self formation of the figure in the story relates to the social institution that exists in society. The method used in this research is Qulitative and presented descriptively and data collection techniques using literature studies. The theory used is that social institution is related to the social background and stage of homosexual self formation by Vivinnie Cass. The results showed Kusakabe's figures fulfilled four stages of the six stages of homosexual self formation. The four stages are Identity Confusion, Identity Comparation, Identity Acceptance, and Identity Synthesis. Identity Confusion stage is related to educational institutions (non-academic curriculum). Identity Comparison relates to religious institutions (ethics). Identity Acceptance relates to religious institutions (ethics). Identity Synthesis is related to the family institutions (marriage) and religious institutions (ethics). In conclusion, Kusakabe did not go through the Identity Tolerance because he did not look for homosexual groups and the Identity Pride because Kusakabe did not think heterosexual was the wrong thing. Although Kusakabe managed to come out as a homosexual, social institutions would not approve of homosexual behavior.